Guido van Rossum: The Early Years of Python. - Severance, Charles (Computer (00189162), 2015)
Guido van Rossum discusses the initial development of Python, which has increasingly become the programming language of choice for many scientific fields due to its extensibility and ease of use. The first Web extra at http://youtu.be/xLVxoz-mQFs is a video in which Guido van Rossum talks with Charles Severance about the birth of the general-purpose, high-level Python programming language. The second Web extra at http://youtu.be/SdH8fI1aNZA is a video in which Guido van Rossum presents a quick introduction of the Python language to students of Computer programming. The third Web extra at http://youtu.be/kFDyvsxX4sg is an audio recording of the Computing Conversations column in which author Charles Severance discusses his interview with Guido van Rossum about the birth of the general-purpose, high-level Python programming language.